Zika virus: Facing a new threat. Issue 8 (August 2016) - Simon, R. Bryan; Carpenetti, Tiffany L.
Abstract : Worried patients are looking to their healthcare providers for information about the Zika virus and their personal risk. Update your knowledge about Zika virus infection, including how it's transmitted and what to teach patients about preventive measures.